SIMULAÇÃO DA RESISTÊNCIA IMPOSTA AO FLUXO POR COBOGÓS ENQUANTO DOMÍNIOS POROSOS - Raviolo, Bruno; Leite, Renan Cid; Cardoso, Daneil; Passos, José Aderson; Catunda, Natasha; Cordeiro, Karoline; Castro, Nayana Helena (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Cobogo's relevanceto brasilian architeture dates back to its modernist movement, allowing adaptation to hot and humid climate and still being applied to new buildings. Contemporary design processes employ new tools to better analyze building performance through computational simulations and building information models. In computational fluid dynamics, however, practical barriers arise when evaluating natural ventilation in buildings that extensively uses cobogós on their facades. This paper investigates those issues in the current methodology and proposes the use of porous domains that mimics the behavior of cobogós. A case study of cobogós used in an experimental building analyzes their characteristics by conducting computational fluid dynamics simulations in a juxtaposed arrangement as well as an isolated element on a wall. Results includes resistance loss coefficients data for geometrically modelled cobogós and their equivalent porous domains, thus evaluating the method's realiability for design processes. Following discussions identify method's potentialities and limitations, as well as future steps and practical applications.